2013
DOI: 10.1039/c3cp52344f
|View full text |Cite
|
Sign up to set email alerts
|

Conformational control of benzophenone-sensitized charge transfer in dinucleotides

Abstract: Charge transfer in DNA cannot be understood without addressing the complex conformational flexibility, which occurs on a wide range of timescales. In order to reduce this complexity four dinucleotide models 1X consisting of benzophenone linked by a phosphodiester to one of the natural nucleosides X = A, G, T, C were studied in water and methanol. The theoretical work focuses on the dynamics and electronic structure of 1G. Predominant conformations in the two solvents were obtained by molecular dynamics simulat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 67 publications
1
15
0
Order By: Relevance
“…9(b)] the data are much clearer and show a good signal-to-noise ratio. The benzophenone excitedstate absorption from the S 1 state at about 580 nm changes to the persistent absorption from the T 1 state the system relaxes to in about 10 ps [37]. A fit to the 550 nm trace from Fig.…”
Section: Improved Spectroscopic Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…9(b)] the data are much clearer and show a good signal-to-noise ratio. The benzophenone excitedstate absorption from the S 1 state at about 580 nm changes to the persistent absorption from the T 1 state the system relaxes to in about 10 ps [37]. A fit to the 550 nm trace from Fig.…”
Section: Improved Spectroscopic Resultsmentioning
confidence: 98%
“…The transient signals of an artificial C-nucleoside with benzophenone as chromophore (compound 1 in [37]) are measured. This compound is only weakly solvable in H 2 O and the dynamics in H 2 O could previously not be measured [37]. The sample is excited at 310 nm with an energy of 150 nJ.…”
Section: Improved Spectroscopic Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It became clear that the solvent, H 2 O or MeOH, controls the conformational distribution and thereby actually gates the charge‐transfer process as a result of differences in the distance and degree of stacking between benzophenone and the second component of the dinucleotide. Our results gave a full understanding of the photophysical properties of the singlet and triplet state of the BP chromophore in the context of each of the four different DNA bases 11. Moreover, these studies clearly revealed that nucleotides that contain conventional benzophenone as the artificial DNA base are not suited to serve as a photochemically inert architecture for benzophenone‐mediated photocatalysis.…”
Section: Introductionmentioning
confidence: 88%
“…The exploration of the benzophenone dinucleotides by time‐resolved transient absorption spectroscopy and theoretical methods, including molecular dynamics, revealed charge‐transfer processes predominantly with guanosine as the second component 11. It became clear that the solvent, H 2 O or MeOH, controls the conformational distribution and thereby actually gates the charge‐transfer process as a result of differences in the distance and degree of stacking between benzophenone and the second component of the dinucleotide.…”
Section: Introductionmentioning
confidence: 99%